Hubungan Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada Industri Tekstil - Kurnia Rizqi Ramadhan; Sri Padmantyo (Prosiding University Research Colloquium, 2022)
This research is aims to analyze the relationship of leadership style and work environment on employee job satisfaction in the textile industry. Productive employees mean employees who have good job satisfaction from good leaders. Work environment is another factor that can increase job satisfaction besides leadership style. Job satisfaction can be an indicator of the success or failure of management in a company. This research is quantitative research. The sampling technique was purposive sampling, and obtained 240 research respondents based on predetermined criteria. Research data in the form of primary data by obtaining data using a print out of a questionnaire. The results of this study indicate that both independent variables have a positive and significant effect on dependent variable. Therefore, the fulfillment of the work environment by the company must be adjusted to existing standards and policies. Then as a leader is required to determine and apply the right leadership style in leading employees. It aims to increase employee job satisfaction and will have a considerable impact in providing good service, work quality, and loyalty.